Thermal power generation cell and thermal power generation method using the same
By using n-type silicon and germanium working electrodes and a solid electrolyte of specific polymers in a thermal utilization power generation battery, combined with the addition of alkali metal ions, the efficiency and durability problems of existing thermoelectric conversion elements are solved, and stable and efficient thermal utilization power generation is achieved.
Patent Information
- Application Number
- CN201980052357.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-08-06
- Filing Date
- 2019-08-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2039-08-06
AI Technical Summary
The existing thermoelectric conversion elements have problems such as high prices for semiconductor materials, narrow usage temperature range and low conversion efficiency, and have weak physical durability, which cannot be used in vibration sites, and have low thermal utilization efficiency.
By combining thermoelectric conversion materials and electrolytes that generate thermally excited electrons and holes, a thermal utilization power generation battery containing n-type silicon and germanium and a solid electrolyte with a molecular weight of 200 to 1,000,000 polymer or derivatives thereof was developed, and alkali metal ions were added to extend the battery life.
It realizes stable thermal utilization power generation, extends battery life, and improves the efficiency and durability of thermal utilization power generation.
Smart Images

Figure GDA0002935675870000021 
Figure GDA0002935675870000061 
Figure GDA0002935675870000071
Abstract
Description
Technical Field
[0001] The present invention relates to a thermal power generation cell and a thermal power generation method using the thermal power generation cell. According to the present invention, thermal power generation can be performed efficiently. Background Art
[0002] In the past, as a heat utilization power generation using geothermal heat or factory waste heat, thermoelectric power generation using the Seebeck effect (Patent Documents 1 and 2, and Non-Patent Document 1) was known, and it was expected to be put into practical use to efficiently utilize thermal energy. As a thermoelectric power generation based on the Seebeck effect, its power generation principle utilizes the phenomenon that voltage is generated when a temperature difference is set for a metal or a semiconductor. Specifically, it is a thermoelectric power generation system that converts thermal energy into electrical energy by giving a temperature difference to a thermoelectric conversion element that combines a p-type semiconductor and an n-type semiconductor.
[0003] However, for the conventional thermoelectric conversion elements utilizing temperature difference, there are problems such as high price of semiconductors constituting the thermoelectric conversion elements, high operating temperature range and low conversion efficiency. There are also problems such as weak physical durability of the joint and inability to be set in places where vibration is applied. In addition, since a temperature difference is required for power generation, the setting place is also limited, and sometimes a cooling device is required to obtain the temperature difference. In particular, since one dimension in the thermoelectric conversion module is used for the temperature difference, the utilization of the heat source becomes two-dimensional utilization, and it is impossible to utilize all the surrounding heat in three dimensions, and there is a disadvantage of low heat utilization efficiency.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2010-147236
[0007] Patent Document 2: Japanese Patent Application Publication No. 2003-219669
[0008] Patent Document 3: International Publication No. WO2017 / 038988
[0009] Non-patent literature
[0010] Non-patent document 1: "Renewable and Sustainable Energy Reviews" (Netherlands), 2014, Vol. 33, p. 371
[0011] Non-patent document 2: "Fusara Solar Battery 3" edited by Keihiro Hamakawa, 2004, Kono Corporation Summary of the invention
[0012] Technical Problems to be Solved by the Invention
[0013] The inventors of the present invention have developed a heat-utilizing power generation cell that can convert thermal energy into electrical energy by combining a thermoelectric conversion material and an electrolyte that generate thermally excited electrons and holes (Patent Document 3). The inventors of the present invention have further studied and found that by using inorganic solid germanium as a thermoelectric conversion material, an excellent heat-utilizing power generation cell can be obtained. However, it is believed that further stability of battery characteristics and extension of battery life are required.
[0014] Therefore, an object of the present invention is to provide a stable heat-utilizing power generation cell.
[0015] Technical means to solve technical problems
[0016] The inventors of the present invention have conducted intensive research on stable heat-utilizing power generation cells and surprisingly found that stable heat-utilizing power generation cells can be obtained by using n-type silicon and germanium for the working electrode and a polymer having a specific repeating unit with a molecular weight of 200 to 1,000,000 or its derivatives for the electrolyte. It has also been found that the battery life can be extended by adding alkali metal ions as additives.
[0017] In addition, the thermal power generation cell in this specification refers to a cell including a positive electrode and / or a negative electrode in a thermal power generation element.
[0018] The present invention is based on the above findings.
[0019] Therefore, the present invention relates to:
[0020] A heat-utilizing power generation cell, comprising: a working electrode containing n-type silicon and germanium, a counter electrode, and a solid electrolyte containing a polymer represented by the following formula (1) with a molecular weight of 200 to 1,000,000 or a derivative thereof, wherein the solid electrolyte contains copper ions or iron ions as an ion source.
[0021]
[0022] In the formula, R 1 is a single bond, oxygen atom, sulfur atom, -NH-, -PH3-, -(P=O)R 6 -, -O-(P=O)HO-, a carbonate group (-O-(C=O)-O-), a carbonyl group, a sulfonyl group, an ester group or an arylenedioxy group (-O-Ar-O-),
[0023] R 2 , R 3 , R 4 and R 5each independently represents a hydrogen atom, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, a hydroxyl group, a cyano group, an amino group, a carboxyl group, an aldehyde group, a methylcarbonyl group, a methylsulfonyl group, a phosphoryl group, a thiol group (-SH), a nitro group, a phenoxy group, a methyl ester group, or a trifluoromethyl group,
[0024] R 6 is an alkylene group having 1 to 3 carbon atoms,
[0025] The repeating units may be the same or a combination of two or more repeating units;
[0026] The heat-utilizing power generation cell according to [1], wherein the solid electrolyte contains alkali metal ions;
[0027] The heat-utilizing power generation cell according to [2], wherein the alkali metal ions are contained in the form of LiCl or KCl;
[0028] The heat-utilizing power generation cell according to any one of [1] to [3], wherein the copper ions are monovalent copper ions and divalent copper ions;
[0029] The heat-utilizing power generation cell according to any one of [1] to [4], wherein in the working electrode, n-type silicon and germanium are stacked with chromium interposed therebetween;
[0030] The heat-utilizing power generation cell according to any one of [1] to [5], wherein the polymer is a polymer selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, polyethylene glycol, polypropylene glycol, polyethylene carbonate and polypropylene carbonate, or a derivative thereof;
[0031] A method for heat-utilizing power generation, comprising the step of heating the heat-utilizing power generation cell described in any one of [1] to [6] to 25° C. or higher to generate power; and
[0032] The method for thermal power generation according to [7], further comprising, after the heating power generation step, a step of leaving the battery in an insulated state, and a step of further heating the thermal power generation battery to 25° C. or higher to generate power.
[0033] In addition, this specification discloses:
[0034] A heat-utilizing power generation cell, comprising: a working electrode containing n-type silicon and germanium, a counter electrode, and a solid electrolyte containing polyethylene glycol or a derivative thereof having a molecular weight of 200 to 600,000, wherein the solid electrolyte contains copper ions or iron ions as an ion source;
[0035] The heat-utilizing power generation cell according to [1], wherein the solid electrolyte contains alkali metal ions;
[0036] The heat-utilizing power generation cell according to [2], wherein the alkali metal ions are contained in the form of LiCl or KCl;
[0037] The heat-utilizing power generation cell according to any one of [1] to [3], wherein the copper ions are monovalent copper ions and divalent copper ions;
[0038] The heat utilization power generation cell according to any one of [1] to [4], wherein in the working electrode, n-type silicon and germanium are stacked with chromium interposed therebetween.
[0039] A method for heat-utilizing power generation, comprising the step of heating the heat-utilizing power generation cell described in any one of [1] to [5] to 25° C. or higher to generate power; and
[0040] The method for thermal power generation according to [6], further comprising, after the heating power generation step, a step of leaving the battery in an insulated state, and a step of further heating the thermal power generation battery to 25° C. or higher to generate power.
[0041] Effects of the Invention
[0042] According to the heat-utilizing power generation cell of the present invention, it is possible to stably perform heat-utilizing power generation. In addition, according to one embodiment of the present invention, it is possible to obtain a heat-utilizing power generation cell with a long life. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Graphs showing CV measurement (a) and discharge measurement (b) of the thermoelectric power generation cell obtained in Example 1.
[0044] Figure 2 Graphs showing CV measurement (a) and discharge measurement (b) of the thermoelectric power generation cell obtained in Example 2.
[0045] Figure 3 Graphs showing CV measurement (a) and discharge measurement (b) of the thermoelectric power generation cell obtained in Example 3.
[0046] Figure 4 Graphs showing CV measurement (a) and discharge measurement (b) of the thermoelectric power generation cell obtained in Example 4.
[0047] Figure 5 Graphs showing CV measurement (a) and discharge measurement (b) of the thermoelectric power generation cell obtained in Example 5.
[0048] Figure 6 The graphs show the CV measurement (a), discharge measurement (b), CV measurement (c) at 80° C., and discharge measurement (d) after standing at room temperature of the thermoelectric power generation cell obtained in Example 6.
[0049] Figure 7 Graphs showing CV measurement (a) and discharge measurement (b) of the thermoelectric power generation cell obtained in Example 7.
[0050] Figure 8 Graphs showing CV measurement (a) and discharge measurement (b) after standing of the thermoelectric power generation cell obtained in Example 8.
[0051] Fig. 9 Graphs showing CV measurement (a) and discharge measurement (b) of the thermoelectric power generation cell obtained in Example 9.
[0052] Fig.10 This is a graph showing the CV measurement of the thermoelectric power generation cell obtained in Example 10.
[0053] Fig.11 Graphs showing CV measurement (a) and discharge measurement (b) of the thermoelectric power generation cell obtained in Example 11.
[0054] Fig.12 This is a graph showing the CV measurement of the thermoelectric power generation cell obtained in Example 12.
[0055] Fig.13 This is a graph showing the CV measurement of the thermoelectric power generation cell obtained in Example 13.
[0056] Fig.14 This is a graph showing the CV measurement of the thermoelectric power generation cell obtained in Example 14.
[0057] Fig.15 Graphs showing CV measurement (a) and discharge measurement (b) of the thermoelectric power generation cell obtained in Example 15.
[0058] Fig.16 Graphs showing CV measurement (a) and discharge measurement (b) of the thermoelectric power generation cell obtained in Example 16.
[0059] Fig.17 Graphs showing CV measurement (a) and discharge measurement (b) of the thermoelectric power generation cell obtained in Example 17 at 70° C., and discharge measurement (c) at 50° C. DETAILED DESCRIPTION
[0060] [1] Heat-utilizing power generation cells
[0061] The heat-utilizing power generation cell of the present invention comprises: a working electrode containing n-type silicon and germanium, a counter electrode, and a solid electrolyte containing a polymer represented by the following formula (1) with a molecular weight of 200 to 1,000,000 or a derivative thereof, wherein the solid electrolyte contains copper ions or iron ions as an ion source.
[0062]
[0063] In the formula, R 1 is a single bond, oxygen atom, sulfur atom, -NH-, -PH3-, -(P=O)R 6 -, -O-(P=O)HO-, a carbonate group (-O-(C=O)-O-), a carbonyl group, a sulfonyl group, an ester group or an arylenedioxy group (-O-Ar-O-),
[0064] R 2 , R 3 , R 4 and R 5 each independently represents a hydrogen atom, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, a hydroxyl group, a cyano group, an amino group, a carboxyl group, an aldehyde group, a methylcarbonyl group, a methylsulfonyl group, a phosphoryl group, a thiol group (-SH), a nitro group, a phenoxy group, a methyl ester group, or a trifluoromethyl group,
[0065] R 6 is an alkylene group having 1 to 3 carbon atoms,
[0066] The repeating units may be the same or a combination of two or more repeating units.
[0067] Examples of the aryledioxy group include a phenylenedioxy group and a naphthylenedioxy group.
[0068] 《Working Electrode》
[0069] The working electrode of the present invention is not particularly limited as long as it contains n-type silicon and germanium. Germanium is a thermoelectric conversion material that generates holes and electrons and can generate about 10 18 / cm 3 of thermally excited electrons and holes.
[0070] N-type silicon is an electron transport material that transports thermally excited electrons generated by thermoelectric conversion materials. N-type silicon is obtained by adding a trace amount of pentavalent elements such as phosphorus as impurities to pure silicon. Pure silicon with 4 valence electrons is an insulator because the electrons do not move, but n-type silicon contains phosphorus with 5 valence electrons, so the excess electron can move freely, thereby becoming a conductor. Examples of pentavalent elements include phosphorus and arsenic.
[0071] As long as the effects of the present invention are obtained, the ratio of n-type silicon to germanium in the working electrode is not particularly limited, but is 1000:1 to 10:1, more preferably 500:1 to 100:1. Within the above range, n-type silicon can efficiently transport thermally excited electrons generated by germanium.
[0072] The working electrode in the present invention can be made, for example, by stacking germanium on n-type silicon. However, when germanium is directly stacked on n-type silicon, the bonding is sometimes weak. Therefore, it is preferred to stack n-type silicon and germanium, for example, with a binder. Examples of the binder include chromium, nickel, titanium, or tin. As long as the n-type silicon and germanium can be firmly bonded, the amount of the binder is not particularly limited. For example, 0.001 to 1 volume part of the binder can be used relative to 100 volume parts of germanium.
[0073] Counter Electrode
[0074] The counter electrode is not limited as long as it can transport electrons, and examples thereof include fluorine-doped tin oxide (FTO), tin-doped indium oxide (ITO), antimony-doped tin oxide (ATO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), zinc oxide (ZnO), indium oxide (In2O3), tin oxide (SnO2), IZO (In-Zn-O) or IGZO (In-Ga-Zn-O). In addition, metals that do not react with copper ions or iron ions, such as titanium, gold, platinum, silver, tungsten, tantalum, stainless steel, graphene, indium, rhodium, chromium, carbon, alloys of these substances, or combinations of these substances, can be cited.
[0075] The counter electrode may be provided as a counter electrode layer or in the form of a wire. In the case of providing the counter electrode layer, it may be manufactured by vacuum evaporation method, spin coating method or the like.
[0076] Solid Electrolytes
[0077] The solid electrolyte contains a polymer represented by the following formula (1) having a molecular weight of 200 to 1,000,000 or a derivative thereof (hereinafter, sometimes referred to as a polymer or the like).
[0078]
[0079] In the formula, R 1 is a single bond, oxygen atom, sulfur atom, -NH-, -PH3-, -(P=O)R 6 -, -O-(P=O)HO-, a carbonate group (-O-(C=O)-O-), a carbonyl group, a sulfonyl group, an ester group or an arylenedioxy group (-O-Ar-O-),
[0080] R 2 , R 3 , R 4 and R 5 each independently represents a hydrogen atom, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, a hydroxyl group, a cyano group, an amino group, a carboxyl group, an aldehyde group, a methylcarbonyl group, a methylsulfonyl group, a phosphoryl group, a thiol group (-SH), a nitro group, a phenoxy group, a methyl ester group, or a trifluoromethyl group,
[0081] R6 is an alkylene group having 1 to 3 carbon atoms,
[0082] The repeating units may be the same or may be a combination of two or more repeating units. The polymer may be a polymer composed of the repeating units of formula (1). In addition, the solid electrolyte may be a solid electrolyte composed of the polymer or a derivative thereof.
[0083] The polymer is not particularly limited as long as it has a repeating unit included in the formula (1), and examples thereof include polyvinylidene fluoride, polyvinyl alcohol, polyethylene glycol, polypropylene glycol, polyethylene carbonate, and polypropylene carbonate.
[0084] As long as the effects of the present invention can be obtained, the two terminal groups are not particularly limited, and examples thereof include a hydrogen atom, a hydroxyl group, an alkyl epoxy group having 1 to 6 carbon atoms, an acryloyl group, an alkyl carboxyl group having 1 to 6 carbon atoms, an alkylamino group having 1 to 6 carbon atoms, an alkyl group having 1 to 6 carbon atoms, an aldehyde group, an alkyl aldehyde group having 1 to 6 carbon atoms, an alkyl amide group having 1 to 6 carbon atoms, an alkyl azide group having 1 to 6 carbon atoms, an alkyl hydrazide group having 1 to 6 carbon atoms, an alkyl isocyanate group having 1 to 6 carbon atoms, an alkyl maleimide group having 1 to 6 carbon atoms, a sulfonyl group, an amino group or a mercapto group, and preferably a hydrogen atom and / or a hydroxyl group.
[0085] In addition, the polymer derivative may have a substituent in the side chain. That is, the hydrogen atom of the side chain may be substituted. The substituent is not particularly limited, and common groups such as amino, carboxyl, alkyl, aryl, glycidyl, cyano, methylsulfonyl, phosphoryl, and nitro can be used.
[0086] The molecular weight of the polymer or its derivative is 200 to 1,000,000, preferably 400 to 100,000, more preferably 400 to 20,000, further preferably 400 to 6,000, and most preferably 600 to 2,000.
[0087] In addition, in this specification, the molecular weight of a polymer or its derivative means the weight average molecular weight measured by gel permeation chromatography (GPC) in terms of polystyrene. As an example of specific measurement conditions of the weight average molecular weight, for example, the following measurement conditions can be given.
[0088] GPC apparatus: HLC-8120 (manufactured by TOSOH Corporation):
[0089] Chromatographic column: TSK gel Multipore HXL-M (manufactured by TOSOH, 7.8 mm ID (inner diameter) × 30.0 cm)
[0090] Eluent: Tetrahydrofuran (THF)
[0091] Polyethylene glycol
[0092] In one embodiment, the solid electrolyte includes polyethylene glycol or a derivative thereof (hereinafter, sometimes referred to as polyethylene glycol or the like) having a molecular weight of 200 to 1,000,000.
[0093] Polyethylene glycol (PEG) is a polymer compound formed by the polymerization of ethylene glycol. n1 That is, the repeating unit of polyethylene glycol is represented by the following formula (2).
[0094]
[0095] The derivatives of polyethylene glycol are not particularly limited, and examples thereof include derivatives in which one or both of the hydrogen atoms (-H) at both ends are substituted by a substituent. Examples of the substituent include an alkyl epoxy group having 1 to 6 carbon atoms, an acryloyl group, an alkyl carboxyl group having 1 to 6 carbon atoms, an alkyl amino group having 1 to 6 carbon atoms, an alkyl group having 1 to 6 carbon atoms, an aldehyde group, an alkyl aldehyde group having 1 to 6 carbon atoms, an alkyl amide group having 1 to 6 carbon atoms, an alkyl azide group having 1 to 6 carbon atoms, an alkyl hydrazide group having 1 to 6 carbon atoms, an alkyl isocyanate group having 1 to 6 carbon atoms, an alkyl maleimide group having 1 to 6 carbon atoms, a sulfonyl group, an amino group, or a mercapto group. Specifically, examples thereof include polyethylene glycol diglycidyl ether, polyethylene glycol diacrylate, H2N-(CH2-CH2-O) n-1 -CH2-CH2-O-CH2-CH2-COOH、H2N-(CH2-CH2-O) n-1 -CH2-CH2-O-CH2-CH2-NH2、HOOC-(CH2-CH2-O) n-1 -CH2-CH2-O-CH2-CH2-COOH,HOOC-CH2-CH2-COO-(CH2-CH2-O) n-1 -CH2-CH2-O-CO-CH2-CH2-COOH or polyethylene glycol dimethacrylate. In addition, the derivative of polyethylene glycol may also have a substituent in the side chain. The substituent is not particularly limited, and common groups such as amino, carboxyl, alkyl, aryl, glycidyl, cyano, methylsulfonyl, phosphoryl, nitro, etc. can be used.
[0096] 《Polypropylene glycol》
[0097] In one embodiment, the solid electrolyte includes polypropylene glycol or a derivative thereof (hereinafter, sometimes referred to as polypropylene glycol or the like) having a molecular weight of 200 to 1,000,000.
[0098] Polypropylene glycol (PPG) is a polymer compound formed by the polymerization of propylene glycol. n-1 The repeating unit of polypropylene glycol is represented by the chemical formula -CH2-CH2(CH3)-OH.
[0099]
[0100] The derivatives of polypropylene glycol are not particularly limited, and one or both of the hydrogen atoms (-H) at the two terminals are substituted by a substituent. As the substituent at the terminal, the substituent described in the project of the above-mentioned polyethylene glycol can be cited, and the specific derivative is also based on the derivative described in the project of the above-mentioned polyethylene glycol. In addition, the derivatives of polypropylene glycol may also have a substituent in the side chain. As the substituent of the side chain, the substituent described in the project of the above-mentioned polyethylene glycol can be cited.
[0101] 《Polyethylene carbonate》
[0102] In one embodiment, the solid electrolyte includes polyethylene carbonate or a derivative thereof (hereinafter, sometimes referred to as polyethylene carbonate or the like) having a molecular weight of 200 to 1,000,000.
[0103] Polyethylene carbonate (PEC) is a polymer compound formed by the polymerization of ethylene carbonate. n-1 The repeating unit of polyethylene carbonate is represented by the chemical formula -CH2-CH2-O-CO-OH.
[0104]
[0105] The derivative of polyethylene carbonate has no particular limitation, and can enumerate the derivatives substituted by one or both substituted groups in the hydrogen atom (-H) at both ends. As the substituent at the end, can enumerate the substituent recorded in the project of above-mentioned polyethylene glycol, and concrete derivative is also as the criterion with the derivative recorded in the project of above-mentioned polyethylene glycol. In addition, the derivative of polyethylene carbonate also can have substituent in side chain. As the substituent of side chain, can enumerate the substituent recorded in the project of above-mentioned polyethylene glycol.
[0106] 《Polypropylene carbonate》
[0107] In one embodiment, the solid electrolyte includes polypropylene carbonate or a derivative thereof (hereinafter, sometimes referred to as polypropylene carbonate, etc.) having a molecular weight of 200 to 1,000,000.
[0108] Polypropylene carbonate (PPC) is a polymer compound obtained by polymerizing propylene carbonate. n-1 The repeating unit of polypropylene carbonate is represented by the chemical formula -CH2-CH2(CH3)-O-CO-OH.
[0109]
[0110] The derivative of polypropylene carbonate is not particularly limited, and one or both of the hydrogen atoms (-H) at the two terminals can be enumerated as the derivative substituted by a substituent. As the substituent at the end, the substituent recorded in the project of the above-mentioned polyethylene glycol can be enumerated, and the specific derivative is also based on the derivative recorded in the project of the above-mentioned polyethylene glycol. In addition, the derivative of polypropylene carbonate also can have a substituent in the side chain. As the substituent of the side chain, the substituent recorded in the project of the above-mentioned polyethylene glycol can be enumerated.
[0111] 《Polyvinylidene fluoride》
[0112] In one embodiment, the solid electrolyte includes polyvinylidene fluoride or a derivative thereof (hereinafter, sometimes referred to as polyvinylidene fluoride, etc.) having a molecular weight of 200 to 1,000,000.
[0113] Polyvinylidene fluoride (PVDF) is a polymer compound formed by the polymerization of difluoroethylene. n That is, the repeating unit of polyvinylidene fluoride is represented by the following formula (6).
[0114]
[0115] The derivatives of polyvinylidene fluoride are not particularly limited, and derivatives in which one or both of the hydrogen atoms (-H) at the two ends are substituted by substituents can be cited. As the substituents at the ends, the substituents described in the items of the above-mentioned polyethylene glycol can be cited, and the specific derivatives are also based on the derivatives described in the items of the above-mentioned polyethylene glycol. In addition, the derivatives of polyvinylidene fluoride may also have substituents in the side chains. As the substituents of the side chains, the substituents described in the items of the above-mentioned polyethylene glycol can be cited.
[0116] Polyvinyl alcohol
[0117] In one embodiment, the solid electrolyte includes polyvinyl alcohol or a derivative thereof (hereinafter, sometimes referred to as polyvinyl alcohol or the like) having a molecular weight of 200 to 1,000,000.
[0118] Polyvinyl alcohol (PVA) is a polymer compound formed by the polymerization of vinyl alcohol.n That is, the repeating unit of polyvinyl alcohol is represented by the following formula (7).
[0119]
[0120] The derivative of polyvinyl alcohol is not particularly limited, and one or both of the hydrogen atoms (-H) at the two terminals are substituted by a substituent. As the substituent at the terminal, the substituent described in the project of the above-mentioned polyethylene glycol can be mentioned, and the specific derivative is also based on the derivative described in the project of the above-mentioned polyethylene glycol. In addition, the derivative of polyvinyl alcohol may also have a substituent in the side chain. As the substituent of the side chain, the substituent described in the project of the above-mentioned polyethylene glycol can be mentioned.
[0121] 《Poly(vinylidene fluoride-co-hexafluoropropylene)》
[0122] In one embodiment, the solid electrolyte includes poly(vinylidene fluoride-co-hexafluoropropylene) or a derivative thereof (hereinafter, sometimes referred to as poly(vinylidene fluoride-co-hexafluoropropylene) etc.) having a molecular weight of 200 to 1,000,000.
[0123] Poly(vinylidene fluoride-co-hexafluoropropylene) is a polymer compound formed by copolymerization of vinylidene fluoride and hexafluoropropylene. x (CF2-C(CF3)F) y That is, the repeating unit of poly(vinylidene fluoride-co-hexafluoropropylene) is represented by the following formula (8).
[0124]
[0125] The derivative of poly (vinylidene fluoride -co- hexafluoropropylene) is not particularly limited, and one or both of the hydrogen atoms (-H) at the two ends are substituted by a derivative. As the substituent at the end, the substituent described in the project of the above-mentioned polyethylene glycol can be cited, and the specific derivative is also based on the derivative described in the project of the above-mentioned polyethylene glycol. In addition, the derivative of poly (vinylidene fluoride -co- hexafluoropropylene) may also have a substituent in the side chain. As the substituent of the side chain, the substituent described in the project of the above-mentioned polyethylene glycol can be cited.
[0126] The solid electrolyte in the present invention refers to a solid electrolyte that is in a quasi-solid state at high temperatures.
[0127] 《Ion Source》
[0128] The ion source included in the solid electrolyte of the present invention is not particularly limited as long as it is copper ion or iron ion, and can include monovalent copper ion, divalent copper ion, divalent iron ion or trivalent iron ion. However, copper ion or iron ion is preferably two stable ions with different valences. This is because the ions on one side are oxidized or reduced to become the ions on the other side, which can transport electrons and holes.
[0129] Therefore, in the case of copper ion, preferably monovalent copper ion and divalent copper ion, in the case of iron ion, preferably divalent iron ion and ferric iron ion. As monovalent copper ion, for example, CuCl, CuBr, copper acetate (I), copper iodide (I) or copper sulfate (I) can be used. As divalent copper ion, CuCl2, CuTSFI2, copper acetate (II), copper sulfate (II) or acetylacetonate copper (II) can be used. As divalent iron ion, Fe (C5H5)2 (ferrocene), K4[Fe (CN)6], acetylacetonate iron (II), iron chloride (II) iron sulfate (II) or iron acetate (II) can be used. As ferric iron ion, FeCl3, K3[Fe (CN)6], acetylacetonate iron (III) or iron sulfate (III) can be mentioned.
[0130] The concentration of the ion source is not particularly limited as long as the effects of the present invention can be obtained, but is preferably added at 0.01 to 98 mol % relative to the polymer, etc. Within the above range, the ion source can efficiently transport electrons and holes.
[0131] The solid electrolyte may contain other components. As other components, there is no limitation, for example, polar solvents (water, methanol, toluene, tetrahydrofuran, etc.) capable of dissolving or dispersing ion sources, binders (polyvinyl alcohol, methylcellulose, acrylic resin, agar, etc.), sintering aids (magnesium oxide, yttrium oxide, calcium oxide, etc.) that are helpful for the formation of hole transport materials, etc. can be cited.
[0132] Adding Materials
[0133] The heat-utilizing power generation cell of the present invention preferably contains alkali metal ions as additive materials. As alkali metal ions, lithium ions, sodium ions, potassium ions, rubidium ions, cesium ions or francium ions can be mentioned, preferably lithium ions, sodium ions or potassium ions. By including alkali metal ions, the battery life can be extended, and the discharge characteristics can be restored by placing it under a heat source. The above-mentioned alkali metal ions are not limited, but are preferably added to the solid electrolyte in the form of halides. As halogens that form halides with alkali metal ions, fluorine, chlorine, bromine, iodine, and astatine can be mentioned. For example, as compounds of alkali metal ions and chlorine, LiCl, NaCl, KCl, RbCl, CsCl or FrCl can be mentioned, preferably LiCl, NaCl or KCl.
[0134] As long as the battery life can be extended, the amount of alkali metal halide (such as LiCl or KCl) added is not particularly limited, but is, for example, 0.001 to 100 parts by weight, preferably 0.01 to 10 parts by weight, and more preferably 0.03 to 0.1 parts by weight, relative to 100 parts by weight of a polymer such as PEG. By being within the above range, a particularly excellent effect of extending the battery life can be obtained.
[0135] Inorganic Oxides
[0136] The heat-utilizing power generation cell of the present invention may include an inorganic oxide, but is not limited thereto. As the inorganic oxide, there is no particular limitation as long as the effect of the present invention can be obtained, and examples thereof include titanium oxide (TiO2), aluminum oxide (Al2O3) or silicon dioxide (SiO2). By including an inorganic oxide, the strength of the solid electrolyte can be increased and short circuits can be prevented.
[0137] "effect"
[0138] Although the mechanism by which the heat-utilizing power generation cell of the present invention can generate electricity stably and exhibit an excellent battery life has not been analyzed in detail, it can be inferred as follows. However, the present invention is not limited to the following inference.
[0139] The thermal power generation cell of the present invention uses a polymer having a specific repeating unit with a molecular weight of 200 to 1,000,000 or a derivative thereof as a solid electrolyte. The thermal power generation method can operate for a long time by controlling the balance between the redox reaction of ions and the diffusion of ions. That is, the key is that the ions oxidized and reduced on the electrode surface reach a redox equilibrium in the electrolyte. By using the above-mentioned polymer or a derivative thereof, the diffusion rate of ions can be effectively controlled even at high temperatures. In addition, in order to increase the range of operating temperatures, a polymer that is stable in high temperature regions is also required, and the thermal power generation cell of the present invention can generate electricity stably.
[0140] Furthermore, the heat-utilizing power generation cell of the present invention can significantly extend the discharge maintenance time of the heat-utilizing power generation cell by including alkali metal ions as additives. It is inferred that the alkali metal ions indirectly interact with the copper ions or iron ions oxidized and reduced on the electrode surface, promoting the diffusion of the copper ions or iron ions into the solid electrolyte. In addition, it is believed that the diffusion of copper ions or iron ions based on the indirect interaction with copper ions or iron ions will be promoted in particular in the insulating state after the end of power generation. Therefore, it is inferred that the discharge characteristics of the heat-utilizing power generation cell can be restored after the insulating state.
[0141] In addition, it is inferred that the above polymer can effectively control the diffusion rate of ions even at high temperatures because it has two carbon atoms in the repeating unit or combination. 2 , R3 , R 4 , R 5 It is a specific group such as an alkyl group, a fluorine atom, a hydroxyl group, etc., which can effectively control the diffusion rate of ions even at high temperatures.
[0142] In the heat-utilizing power generation cell of the present invention, a metal that does not react with copper ions or iron ions, such as a conductor such as titanium, gold, platinum, silver, tungsten, tantalum, stainless steel, graphene, indium, rhodium, chromium, carbon, alloys of these substances, or combinations of these substances, may be attached to the working electrode and / or the counter electrode. In addition, the same material may be used for the working electrode and the counter electrode.
[0143] The conductor may be provided in the form of a wire or may be provided as a conductor layer. When provided as a conductor layer, it may be manufactured by vacuum deposition or spin coating.
[0144] [2] Thermal power generation
[0145] The heat utilization power generation method of the present invention includes a step of heating the above-mentioned heat utilization power generation cell to above 25°C to generate electricity (heating power generation step). As long as the heat utilization power generation cell of the present invention can generate electricity, the heating temperature is not particularly limited. That is, as long as germanium can generate a sufficient number of thermally excited electrons and holes for power generation, and the charge transport ion pair (ion pair) can move in the electrolyte, the heating temperature is not particularly limited, for example, above 25°C, preferably above 35°C, more preferably above 50°C, and further preferably above 80°C. As for the upper limit of the temperature, as long as it is a temperature at which the charge transport ion pair can reciprocate in the electrolyte, there is no particular limitation, for example, below 300°C, preferably below 120°C.
[0146] In addition, the temperature at which the heat-utilizing power generation cell of the present invention actually generates power depends not only on the temperature at which germanium can generate a sufficient number of thermally excited electrons and holes for power generation, but also on the ease of electron movement inherent in the material or the ease of electron movement at the interface between the solid electrolyte and germanium resulting from the combination with the solid electrolyte. These conditions can be appropriately studied.
[0147] In the heat utilization power generation method of the present invention, after the above-mentioned heating power generation process, it can also include a process of placing in an insulating state (placing process), and a process of further heating the heat utilization power generation battery to above 25°C to generate electricity (heating power generation process). The insulating state in the above-mentioned placement process, as an example, refers to the state after the process of cutting off the switch. Through the above-mentioned placement process, ion sources such as copper ions or iron ions diffuse in the solid electrolyte, and efficient heating power generation can be performed. In addition, the battery life can be extended.
[0148] Since diffusion of the ion source will occur even if it is left for several minutes, there is no particular limit to the placement time, but considering the diffusion state of the ion source, the placement time is, for example, more than 1 hour, preferably more than 2 hours, more preferably more than 6 hours, and further preferably more than 12 hours. The longer the placement time, the more diffusion of the ion source will occur, so there is no upper limit, but in order to perform efficient power generation, the upper limit of the placement time is preferably within two days.
[0149] In the heat-utilizing power generation method of the present invention, the above-mentioned placing step and heating power generation step may be repeated two or more times. The number of times the above-mentioned placing step and heating power generation step are repeated is not particularly limited.
[0150] Example
[0151] Hereinafter, the present invention will be specifically described by way of examples, but these examples are not intended to limit the scope of the present invention.
[0152] 《Example 1》
[0153] In this embodiment, PEG600 is used as a solid electrolyte and CuCl is used as an ion source to prepare a thermoelectric power generation cell.
[0154] On n-Si with a thickness of about 0.5 mm, 20 nm of Cr was deposited as a binder, and 2 μm of Ge was further deposited thereon. The structure was cut into 25×15×0.5 mm and used as a working electrode.
[0155] For the counter electrode, fluorine-doped tin oxide (FTO, sheet resistance 7Ω / □, Aldrich) cut into a size of 25×15×2.2 mm was used.
[0156] 0.1 g of PEG600 (Wako) was added to a mortar, and CuCl (0.01 g) was added and stirred for 10 minutes to prepare an electrolyte. The obtained electrolyte (1 μL) was added dropwise to the germanium of the working electrode. A heat-resistant insulating double-sided tape (KAPTON tape with a 5 mm hole) was used as a spacer to bond the germanium side of the working electrode to the FTO of the counter electrode. That is, the electrode area of the power generation unit was a circle with a diameter of 5 mm and was 78.5 square millimeters.
[0157] The obtained battery was placed in a thermostatic chamber. In the CV measurement, the measurement was performed by potential scanning at a scanning rate of 10 mV / sec. In addition, the discharge measurement was performed at 10 nanoamperes. The results are shown in Tables 1 and Figure 1 The power generation characteristics of the open circuit voltage of about 0.2V and the short circuit current of 4 microamperes were observed ( Figure 1 The discharge lasted for more than 2 hours at 10 nanoamperes ( Figure 1 b) in the above.
[0158] 《Example 2》
[0159] In this example, the operation of Example 1 was repeated except that acetonitrile (ACN) was used as an additive material to produce a heat-utilizing power generation cell.
[0160] 0.1 g of PEG600 was added to a mortar, and CuCl (0.01 g) and ACN (0.25 mL) were added as additives. The mortar was left at 80° C. for 20 minutes to evaporate the ACN, thereby preparing an electrolyte. The results are shown in Tables 1 and Figure 2 .
[0161] The power generation characteristics were observed to be approximately 0.2 V for open circuit voltage and 5 μA for short circuit current ( Figure 2 The discharge was stable at about 0.2V at 10 nanoamperes and lasted for about 4 hours ( Figure 2 b) in the above.
[0162] 《Example 3》
[0163] In this example, the operation of Example 2 was repeated except that PEG2000 was used as the solid electrolyte instead of PEG600 to produce a heat-utilizing power generation cell.
[0164] 0.1 g of PEG2000 was added to a mortar, and CuCl (0.01 g) and ACN (0.5 mL) were added as additives, and stirred at 80°C for 10 minutes. The electrolyte was prepared by leaving the mixture at 80°C for 20 minutes to evaporate the ACN. The results are shown in Tables 1 and Figure 3 .
[0165] The power generation characteristics of the open circuit voltage of about 0.2V and the short circuit current of 7 microamperes were confirmed ( Figure 3 The discharge was stable at 10 nanoamperes and lasted for about 4 hours ( Figure 3 b) in the above.
[0166] 《Example 4》
[0167] In this example, the operation of Example 2 was repeated to prepare a heat-utilizing power generation cell, except that a mixture of PEG600 / PEDE500 was used as the solid electrolyte instead of PEG600.
[0168] 0.1 g of PEG600 and 0.1 g of PEDE500 were added to a mortar, and CuCl (0.02 g) and ACN (0.5 mL) were added as additives, and stirred at 80°C for 10 minutes. The electrolyte was prepared by leaving the mixture at 80°C for 20 minutes to evaporate the ACN. The results are shown in Tables 1 and Figure 4 .
[0169] The open circuit voltage was 0.2V and the short circuit current was 1.3 microamperes. Figure 4 The discharge lasted for 6 hours at 10 nanoamperes ( Figure 4 b) in the above.
[0170] 《Example 5》
[0171] In this example, the operation of Example 1 was repeated except that FeCl3 was used as the ion source instead of CuCl to produce a heat-utilizing power generation cell.
[0172] 1 g of PEG600 was added to a mortar, and FeCl3 (0.162 g) was added, and FeCl3 was dissolved in PEG at 80°C to prepare an electrolyte. The results are shown in Tables 1 and Figure 5 .
[0173] The power generation characteristics observed were an open circuit voltage of approximately 0.4 V and a short circuit current of approximately 5 μA ( Figure 5 It was confirmed that the discharge was stable at 10 nanoamperes for about 4 hours ( Figure 5 b) in the above.
[0174] Comparative Example 1
[0175] In this comparative example, the operation of Example 1 was repeated to produce a heat-utilizing power generation cell, except that Ge alone was used as the working electrode instead of n-Si and Ge, and ferrocene was used as the ion source instead of CuCl.
[0176] On n-Si with a thickness of about 0.5 mm, 20 nm of Cr was deposited as a binder, and 2 μm of Ge was further deposited thereon. The structure was cut into 25×15×0.5 mm and used as a working electrode.
[0177] For the counter electrode, fluorine-doped tin oxide (FTO, sheet resistance 7Ω / □, Aldrich) cut into a size of 25×15×2.2 mm was used.
[0178] 0.1 g of PEG600 (Wako) was placed in a mortar, and ferrocene (0.0093 g) was added thereto, followed by stirring for 10 minutes to prepare an electrolyte.
[0179] The open circuit voltage is about 0.5V, while the short circuit current is lower, about 0.1 microamperes, and the discharge maintenance time is also shorter, at 40 minutes.
[0180] Comparative Example 2
[0181] In this comparative example, the operation of Example 1 was repeated except that SnCl2·H2O was used as the ion source instead of CuCl to produce a heat-utilizing power generation cell.
[0182] 0.1 g of PEG600 (Wako) was placed in a mortar, and SnCl2.H2O (0.0226 g) was added thereto, followed by stirring for 10 minutes to prepare an electrolyte.
[0183] No power generation occurred.
[0184] Comparative Example 3
[0185] In this comparative example, the operation of Example 1 was repeated except that PEI500 was used as the solid electrolyte instead of PEG600 to produce a heat-utilizing power generation cell.
[0186] 0.1 g of PEI500 (Wako) was added to a mortar, and CuCl (0.02 g) was added, followed by stirring for 10 minutes to prepare an electrolyte.
[0187] No power generation occurred.
[0188] Example 6
[0189] In this example, the operation of Example 1 was repeated to prepare a heat-utilizing power generation cell, except that CuCl and CuCl2 were used as ion sources instead of CuCl, and LiCl was used as an additive.
[0190] 0.1 g of PEG600 (Wako) was added to a mortar, and CuCl (0.01 g), CuCl2 (0.014 g), and LiCl (0.005 g) as an additive were added, and stirred for 10 minutes to prepare an electrolyte. The results are shown in Table 1 and Figure 6 .
[0191] The power generation characteristics observed were an open circuit voltage of approximately 0.25 V and a short circuit current of approximately 4 microamperes ( Figure 6 a in the figure). It was confirmed that the discharge time at 10 nanoamperes was 505 hours ( Figure 6 b) in the above.
[0192] Furthermore, it was confirmed that the open circuit voltage was about 0.1V and the short circuit current was about 5 microamperes at 35°C. Figure 6 c) It was confirmed that the discharge was 2.5 hours at 100 nanoamperes.
[0193] In addition, after the battery was discharged (1μA), it was left at room temperature for 12 hours and the discharge characteristics (100nA) were confirmed again. In other words, it can be seen that the discharge characteristics are restored by the heat energy at room temperature ( Figure 6 d) in.
[0194] As can be seen from the above, the above-mentioned battery configuration can generate electricity stably, and the discharge characteristics can be restored by the energy at room temperature.
[0195] 《Example 7》
[0196] In this example, the operation of Example 6 was repeated to produce a heat-utilizing power generation cell, except that PEG100000 with a molecular weight of 100,000 was used as the solid electrolyte instead of PEG600.
[0197] 0.5 g of PEG100000 was added to a mortar, and CuCl (0.05 g), CuCl2 (0.07 g), and LiCl (0.1 g) as an additive were added, and stirred at room temperature for 10 minutes. The mixture was vacuum dried at 60°C for 2 hours to prepare an electrolyte. The results are shown in Table 1 and Figure 7 .
[0198] Figure 7 CV measurement at 80°C is shown in FIG. 1. Power generation with an open circuit voltage of 0.35 V and a short circuit current of 8 μA was confirmed. Figure 7 The discharge was stable at 10 nanoamperes for 70 hours ( Figure 7 b) in the above.
[0199] 《Example 8》
[0200] In this example, the operation of Example 6 was repeated except that acetonitrile was further used as an additive material to produce a heat-utilizing power generation cell.
[0201] 0.1 g of PEG600 (Wako) was added to a mortar, and CuCl (0.01 g), CuCl2 (0.014 g), and LiCl (0.005 g) and ACN (0.5 mL) as additives were added, and stirred for 10 minutes to prepare an electrolyte. The results are shown in Table 1 and Figure 8 .
[0202] Figure 8 The CV measurement at 80°C is shown in a. The power generation characteristics of the open circuit voltage of about 0.35 V and the short circuit current of about 6 microamperes were confirmed ( Figure 8 a in the figure). Next, the battery was kept at 80°C and the discharge characteristics at 100 nanoamperes were confirmed. The results showed an average voltage of about 0.4V, and the discharge was completed in about 80 hours. However, after the battery was placed at 80°C for one day, the results again confirmed power generation with an open circuit voltage of 0.5V and a short circuit current of 2 microamperes. This discharge continued for about a day. After further placing it at 80°C for two days, the result was that the discharge characteristics of the open circuit voltage of 0.5V were restored ( Figure 8 b) in the figure, and the discharge lasted for about two days.
[0203] 《Example 9》
[0204] In this example, the operation of Example 6 was repeated except that KCl was used as an additive material instead of LiCl to produce a heat-utilizing power generation cell.
[0205] 0.1 g of PEG600 was added to a mortar, and CuCl (0.01 g), CuCl2 (0.014 g), KCl (0.034 g) as an additive, ACN (0.25 mL), and ethanol (0.25 mL) were added, and stirred at room temperature for 10 minutes. The electrolyte was prepared by vacuum drying at 60°C for 4 hours. The results are shown in Table 1 and Fig. 9 .
[0206] The open circuit voltage was 0.25V and the short circuit current was about 10 microamperes. Fig. 9 The discharge lasted for 120 hours at 10 nanoamperes ( Fig. 9 b) in the above.
[0207]
[0208] 《Example 10》
[0209] In this embodiment, PVDF1000000 is used as a solid electrolyte, and CuCl and CuCl2 are used as ion sources to produce a thermoelectric power generation cell.
[0210] On n-Si with a thickness of about 0.5 mm, 20 nm of Cr was deposited as a binder, and 2 μm of Ge was further deposited thereon, and the resultant structure was cut into a disk with a diameter of 1 cm, and used as a working electrode.
[0211] As a counter electrode, a SUS disk coated with PEDOT / PSS and having a diameter of 1 cm and a thickness of 0.5 mm was used.
[0212] For the electrolyte, add PVDF (0.1 g), CuCl (0.02 g) and LiCl (0.03 g) to a mortar. Add NMP (2 mL) and grind and stir while heating to 60°C. After complete dissolution, add CuCl2 (0.028 g), grind and stir. Spread the resulting gel on a PE film and vacuum dry it. Assemble the test battery in 2035 button battery hardware in a glove box. Set the resulting battery in a constant temperature bath. In the CV measurement, the measurement was performed by potential scanning at a scanning speed of 10 mV / s. The power generation characteristics of an open circuit voltage of approximately 0.48 V and a short circuit current of 12 μA at 80°C were observed ( Fig.10 , Table 2).
[0213] Example 11
[0214] In this embodiment, PPC40000 is used as a solid electrolyte, and CuCl and CuCl2 are used as ion sources to produce a thermoelectric power generation cell.
[0215] On n-Si with a thickness of about 0.5 mm, 20 nm of Cr was deposited as a binder, and 2 μm of Ge was further deposited thereon. The resultant structure was cut into a disk with a diameter of 1 cm and used as a working electrode.
[0216] As a counter electrode, a SUS disk coated with PEDOT / PSS and having a diameter of 1 cm and a thickness of 0.5 mm was used.
[0217] For the electrolyte, add PPC (0.1 g), CuCl (0.02 g) and LiCl (0.03 g) to a mortar. Add 2 mL of NMP and grind and stir while heating to 60°C. After complete dissolution, add CuCl2 (0.028 g), grind and stir. Spread the resulting gel on a PE film and vacuum dry it. Assemble the test battery in 2035 button battery hardware in a glove box. Set the resulting battery in a constant temperature bath. In the CV measurement, the measurement was performed by potential scanning at a scanning rate of 10 mV / s. Power generation characteristics of an open circuit voltage of approximately 0.15 V and a short circuit current of 120 μA at 80°C were observed. The discharge lasted for more than 14 hours at 1 μA ( Fig.11 , Table 2).
[0218] Example 12
[0219] In this embodiment, PPG2000 is used as a solid electrolyte, and CuCl and CuCl2 are used as ion sources to produce a thermoelectric power generation cell.
[0220] On n-Si with a thickness of about 0.5 mm, 20 nm of Cr was deposited as a binder, and 2 μm of Ge was further deposited thereon, and the resultant structure was cut into a disk with a diameter of 1 cm, and used as a working electrode.
[0221] As a counter electrode, a SUS disk coated with PEDOT / PSS and having a diameter of 1 cm and a thickness of 0.5 mm was used.
[0222] For the electrolyte, add PPG (0.1 g), CuCl (0.02 g) and LiCl (0.03 g) to a mortar. Add NMP (2 mL) and grind and stir while heating to 60°C. After complete dissolution, add CuCl2 (0.028 g), grind and stir. Apply the resulting gel on a PE film and vacuum dry it. Assemble the test battery in 2035 button battery hardware in a glove box. Set the resulting battery in a constant temperature bath. In the CV measurement, the measurement was performed by potential scanning at a scanning speed of 10 mV / s. The power generation characteristics of an open circuit voltage of approximately 0.18 V and a short circuit current of 2.1 μA at 80°C were observed ( Fig.12 , Table 2).
[0223] 《Example 13》
[0224] In this embodiment, PPG2000 / PVDF1000000 is used as a solid electrolyte, and CuCl and CuCl2 are used as ion sources to produce a thermoelectric power generation cell.
[0225] On n-Si with a thickness of about 0.5 mm, 20 nm of Cr was deposited as a binder, and 2 μm of Ge was further deposited thereon, and the resultant structure was cut into a disk with a diameter of 1 cm, and used as a working electrode.
[0226] As a counter electrode, a SUS disk coated with PEDOT / PSS and having a diameter of 1 cm and a thickness of 0.5 mm was used.
[0227] For the electrolyte, add PPG (0.05 g), PVDF (0.05 g), CuCl (0.02 g) and LiCl (0.03 g) to a mortar. Add NMP (2 mL) and grind and stir while heating to 60°C. After complete dissolution, add 0.028 g of CuCl2, grind and stir. Apply the resulting gel on a PE film and vacuum dry it. Assemble the test battery in 2035 button battery hardware in a glove box. Set the resulting battery in a constant temperature bath. In the CV measurement, the measurement was performed by potential scanning at a scanning speed of 10 mV / s. The power generation characteristics of an open circuit voltage of approximately 0.35 V and a short circuit current of 110 μA at 80°C were observed ( Fig.13 , Table 2).
[0228] 《Example 14》
[0229] In this embodiment, PEG100000 / PVDF1000000 is used as a solid electrolyte, and CuCl and CuCl2 are used as ion sources to prepare a thermoelectric power generation cell.
[0230] On n-Si with a thickness of about 0.5 mm, 20 nm of Cr was deposited as a binder, and 2 μm of Ge was further deposited thereon, and the resultant structure was cut into a disk with a diameter of 1 cm, and used as a working electrode.
[0231] As a counter electrode, a SUS disk coated with PEDOT / PSS and having a diameter of 1 cm and a thickness of 0.5 mm was used.
[0232] For the electrolyte, add PEG (0.05 g), PVDF (0.05 g), CuCl (0.02 g) and LiCl (0.03 g) to a mortar. Add NMP (2 mL) and grind and stir while heating to 60°C. After complete dissolution, add CuCl2 (0.028 g) and grind and stir. Apply the resulting gel on a PE film and vacuum dry it. Assemble the test cell in 2035 button cell hardware in a glove box. Set the resulting battery in a thermostatic bath. In the CV measurement, the measurement is performed by potential scanning at a scanning speed of 10 mV / sec.
[0233] The power generation characteristics of the open circuit voltage of about 0.1V and the short circuit current of 150μA at 80℃ were observed ( Fig.14 , Table 2).
[0234] Example 15
[0235] In this embodiment, PPC40000 / PVDF1000000 is used as a solid electrolyte, and CuCl and CuCl2 are used as ion sources to produce a thermoelectric power generation cell.
[0236] On n-Si with a thickness of about 0.5 mm, 20 nm of Cr was deposited as a binder, and 2 μm of Ge was further deposited thereon. The resultant structure was cut into a disk with a diameter of 1 cm and used as a working electrode.
[0237] As a counter electrode, a SUS disk coated with PEDOT / PSS and having a diameter of 1 cm and a thickness of 0.5 mm was used.
[0238] For the electrolyte, PPC (0.05 g), PVDF (0.05 g), CuCl (0.02 g), and LiCl (0.03 g) were added to a mortar. NMP (2 mL) was added and ground and stirred while heating to 60°C. After complete dissolution, CuCl2 (0.028 g) was added and ground and stirred. The resulting gel was coated on a PE film and vacuum dried. The test battery was assembled in 2035 button battery hardware in a glove box. The resulting battery was placed in a constant temperature bath. In the CV measurement, the potential was scanned at a scan rate of 10 mV / s. Power generation characteristics of an open circuit voltage of approximately 0.28 V and a short circuit current of 100 μA at 50°C were observed. The discharge lasted for more than 3119 hours at 10 nA ( Fig.15 , Table 2).
[0239] 《Example 16》
[0240] In this embodiment, PPC40000 / PVDF1000000 is used as a solid electrolyte, and CuCl and CuCl2 are used as ion sources to produce a thermoelectric power generation cell.
[0241] On n-Si with a thickness of about 0.5 mm, 20 nm of Cr was deposited as a binder, and 2 μm of Ge was further deposited thereon. The resultant structure was cut into a disk with a diameter of 1 cm and used as a working electrode.
[0242] As a counter electrode, a SUS disk coated with PEDOT / PSS and having a diameter of 1 cm and a thickness of 0.5 mm was used.
[0243] For the electrolyte, add PPC (0.05g), PVDF (0.05g), CuCl (0.02g) and LiCl (0.03g) to a mortar. Add NMP (2mL) and grind and stir while heating to 60°C. After complete dissolution, add CuCl2 (0.028g), grind and stir. Finally, add TiO2 powder and stir. The resulting gel is coated on a PE film and vacuum dried. Assemble the test battery in 2035 button battery hardware in a glove box. The resulting battery is set in a constant temperature bath. In the CV measurement, the measurement is performed by potential scanning at a scanning speed of 10mV / second. Power generation characteristics of an open circuit voltage of approximately 0.28V and a short circuit current of 100μA at 50°C were observed. The discharge lasted for more than 595 hours at 1μA ( Fig.16 , Table 2).
[0244] 《Example 17》
[0245] In this embodiment, PEC250000 / PVA5000 is used as a solid electrolyte, and CuCl and CuCl2 are used as ion sources to make a thermoelectric power generation cell.
[0246] On n-Si with a thickness of about 0.5 mm, 20 nm of Cr was deposited as a binder, and 2 μm of Ge was further deposited thereon. The resultant structure was cut into a disk with a diameter of 1 cm and used as a working electrode.
[0247] As a counter electrode, a SUS disk coated with PEDOT / PSS and having a diameter of 1 cm and a thickness of 0.5 mm was used.
[0248] For the electrolyte, PEC (0.05 g), PVA (0.05 g), CuCl (0.02 g), and LiCl (0.03 g) were added to a mortar. NMP (2 mL) was added and ground and stirred while heating to 60°C. After complete dissolution, CuCl2 (0.028 g) was added and ground and stirred. The resulting gel was coated on a PE film and vacuum dried. The test battery was assembled in 2035 button battery hardware in a glove box. The resulting battery was placed in a thermostatic bath (70°C). In the CV measurement, the potential was scanned at a scan rate of 10 mV / s. Power generation characteristics of an open circuit voltage of approximately 0.45 V and a short circuit current of 35 μA at 70°C were observed. The discharge lasted for more than 294 hours at 100 nA ( Fig.17 , Table 2).
[0249] Furthermore, the obtained battery was placed in a thermostatic chamber (50°C). In the CV measurement, the measurement was performed by potential scanning at a scanning rate of 10 mV / sec. At 50°C, the discharge was continued at 100 nA for more than 381 hours ( Fig.17 , Table 2).
[0250]
[0251] Industrial Applicability
[0252] The thermal power generation cell of the present invention and the thermal power generation method using the cell can be used for small portable power generation devices, geothermal power generation, thermal power generation using automobile waste heat, and thermal power generation using waste heat (waste heat) from substations, steel furnaces, factories or garbage incineration plants.
Claims
1. A heat-utilizing power generation cell, comprising: a working electrode containing n-type silicon and germanium, a counter electrode, and a solid electrolyte containing a polymer having a molecular weight of 200 to 1,000,000 selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, polyethylene glycol, polypropylene glycol, polyethylene carbonate and polypropylene carbonate, or a derivative thereof, wherein the solid electrolyte contains copper ions or iron ions as an ion source.
2. The heat-utilizing power generation cell according to claim 1, wherein: The solid electrolyte further comprises alkali metal ions.
3. The heat-utilizing power generation cell according to claim 2, wherein: The alkali metal ions are contained in the form of LiCl or KCl.
4. The heat-utilizing power generation cell according to any one of claims 1 to 3, wherein The copper ions are monovalent copper ions and divalent copper ions.
5. The heat-utilizing power generation cell according to any one of claims 1 to 3, wherein In the working electrode, n-type silicon and germanium are stacked with chromium interposed therebetween.
6. The heat-utilizing power generation cell according to any one of claims 1 to 3, wherein The solid electrolyte further comprises an inorganic oxide.
7. A method for generating electricity by utilizing heat, comprising: A heating and power generation step of heating the heat-utilizing power generation cell according to any one of claims 1 to 3 to 25°C or higher to generate power.
8. The heat-utilizing power generation method according to claim 7, wherein: After the heating power generation step, the method includes: placing the device in an insulated state; and further heating the heat-utilizing power generation cell to 25° C. or higher to generate power.
Citation Information
Patent Citations
Power generating system comprising power generating element
JP2003219669A
Electric power plant utilizing exhaust heat
JP2010147236A
Thermoelectric power generation element, thermoelectric power generation module including same, and thermoelectric power generation method using same
WO2017038988A1